Operational Performance of an Agile Supply Chain: A Cash to Cash Approach - Prawira, Afghan; ., Syafdinal; Anwar, Asep; Alaeddin, Omar (ExcelingTech, 2019)
In recent business history, operational innovation has a central role in the success stories of businesses like Dell, Toyota and Wal-Mart, and firms are on their way to make the supply chains more agile. The cash conversion cycle is also playing key role in determining the supply chain performance. Therefore, the main objective of the current study is to examine the impact of agile supply chain on the supply chain operational performance of manufacturing firms operating in Indonesia. In addition to that we have also examined the direct and indirect impact of cash conversion cycle in the relationship between agile supply chain and supply chain operational performance. Of the current stud. The data is collected from the operation managers, production managers and finance managers of manufacturing firms listed in Indonesian Stock Exchange. The results of the study have shown a great deal of agreement with our proposed hypothesis. The study which is among pioneering studies on the issue will be helpful for policy makers and managers in understanding the role of agency theory in supply chain management.